Matching-adjusted indirect comparison between asciminib and flumatinib as first-line treatment for chronic myeloid leukemia in China - Wang, Ying; Hui, Yan; Zhang, Li; Li, Yan; Tang, Meng; Gao, Xue; Zhen, Bihong; Choubey, Abhay; Gupta, Soni; Wei, Hui; Liu, Bingcheng (Translational Cancer Research, 2026)
Background: Asciminib, a novel BCR::ABL1 inhibitor that functions by specifically targeting the myristoyl pocket, has shown superior efficacy and favorable safety and tolerability compared with adenosine triphosphate-competitive tyrosine kinase inhibitors (TKIs) in patients with newly diagnosed chronic myeloid leukemia in chronic phase (CML-CP). Flumatinib, a second-generation TKI available exclusively in China, has not been directly compared with asciminib. Therefore, an anchored matching-adjusted indirect comparison was conducted through use of data from the ASC4FIRST and FESTnd trials.Methods: Imatinib was the common comparator across the ASC4FIRST (NCT04971226) and FESTnd (NCT02204644) trials. To match the two populations, effect modifiers and baseline variables were identified. Adjusted estimates were derived from individual patient-level data (ASC4FIRST) for asciminib and imatinib and from aggregate data for flumatinib (FESTnd). Outcomes were compared based on early molecular response (EMR), major molecular response (MMR), and treatment discontinuation due to adverse events (AEs).Results: Asciminib demonstrated significantly higher EMR rates at 12 weeks (adjusted: 90.0%) than did flumatinib (82.1%), yielding a significantly higher odds ratio [odds ratio (OR): 1.95; 95% confidence interval (CI): 1.05–3.73; P=0.03]. MMR rates, both at 48 and 96 weeks, were significantly higher for asciminib (adjusted: 66.5% and 74.0%, respectively) than for flumatinib (an estimated 52.6% and 61.3%, respectively), with an OR of 1.79 (95% CI: 1.17–2.75; P=0.006). Safety analysis showed fewer discontinuations due to AEs at 48 weeks with asciminib (5.5%) than with flumatinib (10.2%), corresponding to a significantly lower risk of discontinuation due AEs (risk ratio: 0.29; 95% CI: 0.10–0.84; P=0.02).Conclusions: A robust statistical model indicated that asciminib provides consistently superior efficacy and safety over flumatinib, supporting its value as a first-line treatment option for patients with CML-CP.